The role of probiotics in the process of improvement of patients after arterial repair operations - Agnieszka Wilczyńska; Katarzyna Korabiusz; Agata Wawryków; Martyna Maciejewska; Monika Stecko; Anna Fabian-Danielewska; Inga Janik-Fuks (Kazimierz Wielki University, 2019)
This paper aims to is to review the literature on the relationship between microbiota and the immune system in terms of the quality of life of patients after arterial repair operations. Angiology is a branch of medicine dealing with vascular diseases of the blood and lymphatic system. As a sub-discipline of surgery, together with techniques of surgical radiology, it has gained high recognition in the medical environment. Despite increasing progress in the process of arterial repair, postoperative complications in the form of swelling of the lower extremities of the operated side are still a problem. This problem concerns about 6% of patients. Another problem is the risk of vascular transplant infection. The high mortality rate estimated at 9% is worrying. Equally alarming is the percentage of limb amputations at the level of the shin or thigh. It should also be emphasized that the above complications may significantly indicate weakened immunity of patients, thus translating into the slower tissue regeneration process. Even the increasing degree of emotional disturbances as a result of weakened microflora.